The double helix model: Dynamic evolution of knowledge absorptive capacity and innovation efficiency - Liangyou Cheng; Yong Qiu; Luwei Wang (PLoS ONE, 2025)
This study aims to propose a “double helix” dynamic evolution model of absorptive capacity and innovation efficiency, breaking through traditional linear cognition and revealing the synergistic growth patterns between the two. The research focuses on factors such as absorptive capacity, innovation efficiency, policy environment, and knowledge spillovers, using panel data from 29 countries spanning 1960–2023. By employing fixed-effects models, instrumental variable methods, and constructing composite indicators to measure core variables, the study analyzes the relationships through grouped regressions and robustness checks. The findings reveal a marginally enhancing convex positive effect of absorptive capacity on innovation efficiency. The policy environment strengthens this promoting effect by optimizing the institutional context. In high knowledge spillover environments, the convex relationship remains stable, while in low spillover environments, excessive absorptive capacity suppresses efficiency. Heterogeneity analysis shows that absorptive capacity plays a more significant role in the early stages of economic development and before 2000. Theoretically, this study improves the framework of innovation efficiency, and practically, it provides a basis for formulating precise innovation policies and dynamically adjusting innovation strategies for enterprises.